Análise das medidas governamentais de proteção do comércio - Piccoli, Claudio Fiorelli (My University, 2019)
The following work aims to analyze the impacts of actions related to changes in the standards or procedures of foreign trade in the United States, Brazil, Argentina, Peru, Colombia, Mexico and Uruguay against other countries. In order to obtain relevant information to how these countries behave against others and the impact when there is a change of standards or methods to imports and exports to other countries, as well as to determine their main concerns when the current scenario of International trade and the measures that tend to be the most taken as a precaution. The characteristics of each of these actions will be study as well as their final impact leading to the current global context.(sic)
O seguinte trabalho tem como objetivo analisar os impactos das ações relacionadas com mudanças de normas ou procedimentos de comércio exterior do Estados Unidos, Brasil, Argentina, Peru, Colômbia, México e Uruguai quanto a outros países de modo a obter informações relevantes de como esses territórios se comportam perante aos demais e o impacto quando ocorre uma mudança de regulamentos ou métodos quanto as importações e exportações para outras pátrias, assim como determinar as suas principais preocupações quando ao cenário atual do mercado internacional e as medidas que tendem a serem as mais tomadas por precaução. As características de cada uma dessas ações serão estudadas assim como o seu impacto final levando o contexto global atual.(sic)
Keywords: Comércio internacional; Taxas; Importação; Exportação